HUBUNGAN ANTARA KONSUMSI MAKANAN KARIOGENIK DENGAN KEJADIAN KARIES GIGI PADA ANAK SDN 1 GOGODALEM KEC. BRINGIN KAB. SEMARANG - Agus Rosidi; Siti Haryani; Eka Adimayanti (Universitas Muhammadiyah Semarang, 2014)
Dental health problems in Indonesia is still a public health problem. Factors affecting the incidence of dental caries among others: microorganisms, food waste, surface and shape of theteeth, saliva degrees, consumption of cariogenic foods, age. The purpose of this study was todetermine the relationship between the consumption of cariogenic foods with the incidence ofdental caries in children at SDN 1 Gogodalem. This study used observational analytic design with cross sectional approach. Thepopulation in this study were all children who attend school at SDN 1 Gogodalem.The samplesused were elementary school class II-V that totaled 47 children. Sampling technique using totalsampling. Data collection using question naires. Data analysis using the chi-square test. The results obtained by 40 (85.1%) children who consume foods high cariogenic. The Children who suffer from dental caries by 40 (85.1%) children. The incidence of dental caries inchildren at high cariogenic foods (85.1%) and the results obtained by analysis of the value of p= 0.000 so it concluded there was a relationship between the consumption of cariogenic foodswith dental caries experience in children SDN 1 Gogodalem.Researchers suggested in elementary school children to consume nutritious foods and donot forget to brush their teeth twice a day after breakfast and at night before bed in order toprevent the occurrence of dental caries. Keywords: consumption of cariogenic foods, dental caries